Financial Self-Control in Accounting Education Students Universitas Muhammadiyah Surakarta - Hendawan, Muhammad Habil Azhar; Asmawan, Moh. Chairil (Proceedings International Conference on Education Innovation and Social Science, 2023)
Financial self-control in students is closely related to daily life, self-control will also affect what can later be useful or detrimental to the student. Like the behavior of self-control over finances that students do well, it will be beneficial for these students such as perceived welfare. Therefore, the objectives of this study are (1) how students control themselves over finances related to their lifestyle every day, (2) awareness through financial self-control will lead students' attitudes and behaviors towards saving culture. The research method used is a case study with data collection techniques through observation, interviews, and documentation.Through objects regarding financial self-control behavior carried out by students on saving behavior, with subjects namely students, peers, and parents. The results of this study (1) The majority of students allocate pocket money obtained for transportation needs, boarding needs, and meals. (2) The majority of students have been equipped by parents regarding financial literacy in the family, so with that the majority of students can apply saving behavior. However, there are some students who cannot do saving behavior with factors such as lack of pocket money given by parents.